1999
DOI: 10.1114/1.143
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Leukocyte Deformation and Adhesion to Endothelium in Shear Flow

Abstract: The mechanics of leukocyte [white blood cell (WBC)] deformation and adhesion to endothelial cells (EC) in shear flow has been investigated. Experimental data on transient WBC-EC adhesion were obtained from in vivo measurements. Microscopic images of WBC-EC contact during incipient WBC rolling revealed that for a given wall shear stress, the contact area increases with time as new bonds are formed at the leading edge, and then decreases with time as the trailing edge of the WBC membrane peels away from the EC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 28 publications
8
137
0
Order By: Relevance
“…According to Xue et al 4 , the results of several studies show that inorganic nanoparticles can be deposited on the contact surface and improve the tribological properties of the base oil. It was also noted by Xue et al 4 and Dong et al 5 that nanoparticles exhibit good characteristics of adhesion and reduction of wear, even at concentrations below 2 wt.%.…”
Section: Introductionmentioning
confidence: 92%
“…According to Xue et al 4 , the results of several studies show that inorganic nanoparticles can be deposited on the contact surface and improve the tribological properties of the base oil. It was also noted by Xue et al 4 and Dong et al 5 that nanoparticles exhibit good characteristics of adhesion and reduction of wear, even at concentrations below 2 wt.%.…”
Section: Introductionmentioning
confidence: 92%
“…Shear stress dictates the forces applied to cells individually (i.e., increase the extent of cell deformation) or on the intermolecular bonds between cells. A previous study (9) has shown that drag force that disrupts individual adhesive bonds between cells reduces when vessel size increases under a constant shear stress. Therefore, when melanoma cells travel with the bloodstream through capillaries, the shear stress would have different effects on the adhesion interaction of melanoma cell with EC.…”
Section: Discussionmentioning
confidence: 99%
“…50 Other computational models have demonstrated that there are numerous determinants of cell rolling velocities, in addition to a receptor's affinity for its ligand. 49 Previous work has predicted the effects of leukocyte deformability on adhesion kinetics, 18,39 as well as the kinetics of integrin and L-selectin mediated neutrophil aggregation under flow. 107 All of these computational models are highly detailed and mechanistically informative, but they neglect the overall spatial and temporal dynamics within entire tissues.…”
Section: Discussionmentioning
confidence: 99%